Procedures in Implantology, Prosthodontics and Surgery - Pelegrine, André Antonio (Cambridge Scholars Publishing, 2021)
This book describes the most commonly used techniques in Oral Rehabilitation. It has been designed in a step-by-step manner, using study models to standardize how procedures should be performed in an ideal scenario. In this textbook, every chapter contains the description of a technique, its aim and the rationale for each step, which provides students with the tools to grasp the logical reasoning behind each procedure. The volume is divided into three parts: (1) Surgery; (2) Tooth-supported prosthodontics and (3) Implant-supported prosthodontics.This textbook is rich in photographic images and.